Evaluating the Student–Teacher Relationship Scale in Italian Young Children: An Exploratory Structural Equation Modeling Approach. (June 2018) - Sette, Stefania; Zuffianò, Antonio; Lucidi, Fabio; Laghi, Fiorenzo; Lonigro, Antonia; Baumgartner, Emma
The study analyzed the factorial and concurrent validity of the Student–Teacher Relationship Scale (STRS) using an exploratory structural equation modeling (ESEM) approach. Participants were 368 Italian children aged 3 to 6 ( M = 4.60, SD = 0.98). The three-factor ESEM solution fit the data better than the classical confirmatory factor analysis (CFA) model and the measurement invariance of the scale was confirmed across sex and age (3-4 vs. 5-6 years) groups. The concurrent validity of the STRS was investigated within the ESEM approach using children's social behaviors as validity criteria. Findings supported the goodness of ESEM over CFA and attested to the validity of the STRS to understanding the teacher–child relationship quality in young children.